Income elasticity of willingness-to-pay for a carbon tax in Greece. (2018) - Nastis, Stefanos A.; Mattas, Konstadinos
Climate change policy is steadily gaining momentum and is being implemented at the national and international level. The European Union has been committed to control and reduce greenhouse gas emissions, implementing rigorous climate change policy. The aim of this study is to provide the first willingness-to-pay and income elasticity of willingness-to-pay estimates for the reduction of greenhouse gas emissions through a carbon tax in Greece. Based on a survey of 1, 393 adults, households are willing to pay, on average, an annual carbon tax of 81 for the next ten years in order to reduce greenhouse gas emissions by 17% by 2025. Furthermore, results confirm that income elasticity of willingness-to-pay for climate change is not constant, but increases with income, from 0.48 for low income households to 1.40 for high income households. The full sample income elasticity of WTP was estimated at 0.96, raising distributional questions regarding the social profitability of any climate change policy and the probability of public acceptance.